Transcriptional and epigenetic mechanisms of cellular reprogramming to induced pluripotency. (August 2016) - van den Hurk, Mark; Kenis, Gunter; Bardy, Cedric; van den Hove, Daniel L; Gage, Fred H; Steinbusch, Harry W; Rutten, Bart P
Enforced ectopic expression of a cocktail of pluripotency-associated genes such as Oct4, Sox2, Klf4 and c-Myc can reprogram somatic cells into induced pluripotent stem cells (iPSCs). The remarkable proliferation ability of iPSCs and their aptitude to redifferentiate into any cell lineage makes these cells a promising tool for generating a variety of human tissue in vitro . Yet, pluripotency induction is an inefficient process, as cells undergoing reprogramming need to overcome developmentally imposed epigenetic barriers. Recent work has shed new light on the molecular mechanisms that drive the reprogramming of somatic cells to iPSCs. Here, we present current knowledge on the transcriptional and epigenetic regulation of pluripotency induction and discuss how variability in epigenetic states impacts iPSCs' inherent biological properties.